Implementation of a Generative Computer-Assisted Instruction System on a Small Computer - LeFaivre, Rick (University of Wisconsin-Madison Department of Computer Sciences, 1973)
This paper gives a brief overview of several "traditional" approaches towards computer-assisted instruction (CAI. A new CAI language is then described which allows the user to write programs which generate bath questions and answers with a minimum of programming effort. An implementation of the described system is discussed in detail, followed by a description of a sample program which drills the student in German-English translation by generating sentences whose complexity is a function of performance.